1. PERAN UNIVERSITAS DALAM MENINGKATKAN JUMLAH NASABAH BANK BNI: Universitas, Jumlah Nasabah Bank BNI ,Metode kualitatif - Muzammil, Muhammad ghurran faizul muhajjilin; Taufiqurrahman; Wijayanto, Erik; Kafin, Achmad (LP2M IBK Nitro, 2025)
Universities have a significant contribution in increasing the number of customers and strengthening relationships between financial institutions, such as banks and cooperatives, and the surrounding communities. The following is an explanation of how universities can play a role in increasing the number of clients and encouraging more positive responses from them. The Role of Universities in Increasing the Number of Customers: 1. Financial Literacy: Universities can become centers of financial education for students, lecturers and the surrounding community. By holding seminars, training or workshops on financial literacy, universities contribute to expanding knowledge about banking products, investments and financial management. This can motivate more people to become customers. 2. Institutional Partnerships: Many universities partner with banks or other financial institutions to open branch offices, ATMs, or provide digital financial services on campus. This facility makes it easier for the academic community to access banking services, thereby increasing the number of customers. Qualitative methods are research approaches used to understand social or cultural phenomena in an in-depth and holistic way. This method emphasizes understanding the context, perspective, and experiences of research subjects, often using non-numerical data such as interviews, observations, and text analysis.1. Introduction to Banking Services for Students and Staff 2. Opening a Student Account and Payment of Tuition Fees 3. Scholarship Program and Ease of Access to Finance 4. Promotion and Financial Literacy on Campus 5. Digital Innovation in Banking Services 6. Student Involvement in Internship Programs and Bank Activities Collaboration between Zaha University and Bank BNI has great potential to increase the number of bank customers, especially among students and academic staff. By providing banking services that suit student needs, such as low-cost savings accounts or educational loan facilities, Bank BNI can build stronger relationships with the campus community. Apart from that, the use of digital technology and scholarship or internship programs involving students can speed up this process. However, the challenges of facing competition and ensuring that bank services truly meet student needs remain concerns that need to be managed effectively.